2010
DOI: 10.1111/j.1369-1600.2009.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors in frontal cortex and hippocampus of alcohol consumers

Abstract: et al. 1990; Dodd et al. 1992; Freund & Anderson 1996, 1999 Ridge et al. 2008).Our hypothesis is that permanent neuronal damage produced by chronic alcohol consumption is in part due to progressive changes in NMDA receptors, and that these changes might develop before the beginning of clinical manifestations of chronic alcoholism, including dependence, craving and abstinence. Thus, we assessed here the density of NMDA receptors in frontal cortex and hippocampus -brain areas known to be notably affected by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…NMDAR ligand binding in human post-mortem brains is increased in cortical and limbic areas of alcoholics in some (Freund and Anderson 1999), but not other studies (Villegas et al 2011)—perhaps reflecting differences in the extent of alcohol exposure, ante-mortem duration of abstinence, and cumulative effects of alcohol-related neurotoxicity. Abstinent alcoholics have also been shown to have an attenuated response to the perceptual and cognitive effects of the NMDAR antagonist ketamine (Krystal et al 2003).…”
Section: Glutamatergic Targetsmentioning
confidence: 84%
“…NMDAR ligand binding in human post-mortem brains is increased in cortical and limbic areas of alcoholics in some (Freund and Anderson 1999), but not other studies (Villegas et al 2011)—perhaps reflecting differences in the extent of alcohol exposure, ante-mortem duration of abstinence, and cumulative effects of alcohol-related neurotoxicity. Abstinent alcoholics have also been shown to have an attenuated response to the perceptual and cognitive effects of the NMDAR antagonist ketamine (Krystal et al 2003).…”
Section: Glutamatergic Targetsmentioning
confidence: 84%
“…Recent research showed that oxidation of [13]C-acetate generates specific neurotransmitters, as [13]C-glutamine, glutamate, and GABA levels were higher in chronic ethanol-exposed rats than in controls [ 86 ]. The production of these molecules may be related to the known effects of GABA receptors [ 16 , 17 , 19 , 117 ], although other receptors are also involved in the effects of ethanol, such as dopamine, acetylcholine, and NMDA receptors [ 118 120 ] ( Figure 2 ).…”
Section: Metabolism Of Ethanol and Acetate In The Brainmentioning
confidence: 99%